Promising Directions of Synergetic Research - Bozarov Dilmurod Mirzarasulovich (Scientific Trends, 2025)
This article explores the current trends in the development of synergetics and its potential applications in interdisciplinary research. It examines the processes of self-organization in complex systems, mechanisms for maintaining stability under uncertainty, and the prospects for applying the synergetic approach in natural, social, and technological systems.
Keywords: Synergetics, complex systems, self-organization, stability, interdisciplinary approach, evolutionary processes.